Indoor air quality and respiratory health among Malay preschool children in Selangor - Mohd Nor Rawi, Nur Azwani; Jalaludin, Juliana; Chua, Poh Choo (Hindawi Publishing Corporation, 2015)
Indoor air quality (IAQ) has been the object of several studies due to its adverse health effects on children. Methods. A cross-sectional comparative study was carried out among Malay children in Balakong (2 studied preschools) and Bangi (2 comparative preschools), Selangor, with the aims of determining IAQ and its association with respiratory health. 61 and 50 children aged 5-6 years were selected as studied and comparative groups. A questionnaire was used to obtain an exposure history and respiratory symptoms. Lung function test was carried out. IAQ parameters obtained include indoor concentration of particulate matter (PM), volatile organic compounds (VOCs), carbon monoxide (CO), carbon dioxide (CO2), temperature, air velocity (AV), and relative humidity. Results. There was a significant difference between IAQ in studied and comparative preschools for all parameters measured (P < 0.001) except for CO2 and AV. Studied preschools had higher PM and CO concentration. FVC, FEV1, FVC% and FEV1% predicted values were significantly lower among studied group. Exposures to PM, VOCs, and CO were associated with wheezing. Conclusion. The finding concluded that exposures to poor IAQ might increase the risk of getting lung function abnormality and respiratory problems among study respondents.